Immunosuppression use in primary antiphospholipid antibody-positive patients: Descriptive analysis of the AntiPhospholipid Syndrome Alliance for Clinical Trials and InternatiOnal Networking (APS ACTION) Clinical Database and Repository ("Registry"). (December 2022) - Erton, Zeynep B; K Leaf, Rebecca; de Andrade, Danieli; Clarke, Ann E; Tektonidou, Maria G; Pengo, Vittorio; Sciascia, Savino; Ugarte, Amaia; Belmont, H. Michael; Gerosa, Maria; Fortin, Paul R; Lopez-Pedrera, Chary; et al.
Background/Purpose: APS ACTION Registry was created to study the outcomes of patients with persistently positive antiphospholipid antibodies (aPL) with or without other systemic autoimmune disease (SAIDx). Given that immunosuppression (IS) is used for certain aPL manifestations, for example, thrombocytopenia (TP), our primary objective was to describe the indications for IS in aPL-positive patients without other SAIDx. Secondly, we report the type of IS used in patients with selected microvascular or non-thrombotic aPL manifestations. Methods: An online database is used to collect clinical data. The inclusion criteria are positive aPL based on the laboratory section of the APS Classification Criteria, tested at least twice within one year prior to enrollment. Patients are followed every 12 ± 3 months. For this descriptive retrospective and prospective analysis, we included aPL-positive patients without other SAIDx and excluded those with new SAIDx classification during follow-up. For each patient, we retrieved clinical data at baseline and follow-up including selected aPL manifestations (diffuse alveolar hemorrhage [DAH], antiphospholipid-nephropathy [aPL-N], livedoid vasculopathy [LV]-related skin ulcers, TP, autoimmune hemolytic anemia [AIHA], cardiac valve disease [VD]), and IS medications. Results: Of 899 patients enrolled, 537 were included in this analysis (mean age 45 ± 13 years, female 377 [70%], APS Classification in 438 [82%], and at least one selected microvascular or non-thrombotic aPL manifestation in 141 (26%)). Of 537 patients, 76 (14%) were reported to use IS (ever), and 41/76 (54%) received IS primarily for selected aPL manifestation. In six of 8 (75%) DAH patients, 6/19 (32%) aPL-N, 4/28 (14%) LV, 25/88 (28%) TP, 6/11 (55%) AIHA, and 1/43 (2%) VD, the IS (excluding corticosteroids/hydroxychloroquine) indication was specific for selected aPL manifestation. Conclusion: In our international cohort, 14% of aPL-positive patients without other SAIDx were reported to receive IS; the indication was at least one of the selected microvascular and/or non-thrombotic aPL-related manifestations in half. Thrombocytopenia was the most frequent among those selected aPL-related manifestations; however, approximately one-third received IS specifically for that indication. Diffuse alveolar hemorrhage was frequently treated with IS followed by AIHA and aPL-N. Systematic controlled studies are urgently needed to better define the role of IS in APS.